2023
DOI: 10.3390/bs13030208
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Symptom Severity of Autism Spectrum Disorder and Screen Time among Toddlers Aged 16 to 36 Months

Abstract: There is growing evidence that prevalence rates of autism spectrum disorder (ASD) are increasing. A number of factors appear to contribute to this increase, including excessive screen time. Screen time seems to be linked to the severity of the symptoms of ASD. Given this, the aim of the present cross-sectional study was to investigate the association between early screen time and ASD symptoms severity in the first 36 months of life. To this end, sixty-eight Iranian toddlers (mean age: 27.09 months; 22.1% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial systematic literature search yielded 4682 records (Figure 1). The first filtering step resulted in 145 studies, and the second filtering step resulted in a final collection of 46 studies that examined the association between screen time and ASD (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on data collected since the COVID-19 pandemic (Table 1). Notably, the research design of all 46 studies was observational: 41 were cross-sectional and 5 were longitudinal . Accordingly, the overall research quality of these studies was determined to be relatively low (according to the GRADE approach) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on these findings, it is recommended that future studies adopt longitudinal designs to more accurately ascertain the longterm impacts of screen time on language development. Moreover, there is a need to explore the qualitative aspects of screen time, such as content type and interactivity level, to determine more precisely how different screen activities contribute to phonological awareness and overall language development (20).…”
Section: Discussionmentioning
confidence: 99%